Transient model of an RSW system with CO2 refrigeration – A study of overall performance. (February 2018) - Brodal, Eivind; Jackson, Steve; Eiksund, Oddmar
Highlights: Thermodynamics based analysis of CO2 -refrigeration in RSW units. Assessment of ambient temperature impact on performance parameters. Modeling of realistic operating parameter for RSW units on board fishery vessels. Detailed exchanger performance modeling instead of fixed temperature approaches. Abstract: Refrigerated seawater (RSW) cooling using CO2 based refrigeration is a relatively new technology that shows promising performance in cold climates. For being a refrigerant CO2 has a low global warming potential (GWP) and is therefore recognized as an environmentally friendly alternative if the unit is competitive on energy efficiency. However, RSW systems with CO2 have a significant reduction in energy efficiency if operated in warm seawater due to its low critical temperature. This study investigates the impact ambient temperature and precooling processes have on performance. The results show that for a fixed process design, lower ambient temperature in the Barents Sea results in an average COP of 5.0 compared with 3.0–3.5 in the Mediterranean Sea, or alternatively, that a ship can operate with RSW tanks that are approximately three times bigger if ambient seawater temperature is 10  °C compared to 20  °C. The study also finds that for a fixed ambient temperature case, the RSW tank can be 3.6–1.8 times larger if one third of the tank volume is precooled.